2010
DOI: 10.1111/j.1365-2796.2009.02151.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atorvastatin on circulating CD34+/CD133+/ CD45− progenitor cells and indices of angiogenesis (vascular endothelial growth factor and the angiopoietins 1 and 2) in atherosclerotic vascular disease and diabetes mellitus

Abstract: Abstract. Jaumdally RJ, Goon PKY, Varma C, Blann AD, Lip GYH (City Hospital, Birmingham, United Kingdom). Effects of atorvastatin on circulating CD34+ ⁄ CD133+ ⁄ CD45) progenitor cells and indices of angiogenesis (vascular endothelial growth factor and the angiopoietins 1 and 2) in atherosclerotic vascular disease and diabetes mellitus. J Intern Med 2010; 267: 385-393.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 59 publications
0
27
1
1
Order By: Relevance
“…In addition to their lipid-lowering effect, statins have many pleiotropic effects that may explain their cardiovascular benefit. Both experimental 81,82 and clinical studies 83 demonstrate that statins increase the number and function of circulating EPCs by increasing the bioavailability of NO and reducing oxidative stress and apoptosis of EPCs. Blockade of the renin-angiotensin system with angiotensinconverting enzyme inhibitors or angiotensin receptor blockers has also been shown to increase EPC number in patients with DM, 84,85 possibly mediated by their anti-inflammatory and antioxidative actions through the suppression of angiotensin II.…”
Section: Approaches To Improve Epc Function and Survivalmentioning
confidence: 99%
“…In addition to their lipid-lowering effect, statins have many pleiotropic effects that may explain their cardiovascular benefit. Both experimental 81,82 and clinical studies 83 demonstrate that statins increase the number and function of circulating EPCs by increasing the bioavailability of NO and reducing oxidative stress and apoptosis of EPCs. Blockade of the renin-angiotensin system with angiotensinconverting enzyme inhibitors or angiotensin receptor blockers has also been shown to increase EPC number in patients with DM, 84,85 possibly mediated by their anti-inflammatory and antioxidative actions through the suppression of angiotensin II.…”
Section: Approaches To Improve Epc Function and Survivalmentioning
confidence: 99%
“…It was demonstrated that angiogenesis is also modified by diabetes-related mechanisms [20,21,22], but there are only a few studies analyzing the serum levels of angiogenesis-promoting factors among patients with type 2 diabetes treated with statins [23,24]. Moreover, most clinical studies concern statins given at high doses (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…LDL-C is inversely correlated with EPC number and function in human patients (Chen, Zhang et al 2004). Statin therapy has been shown to increase EPC numbers and function (Fadini, Albiero et al 2010;Jaumdally, Goon et al 2010) and to enhance EPC numbers in response to ischemic stimuli (Spadaccio, Pollari et al 2010;Hibbert, Ma et al 2011). The improvement of endothelial function associated with statin use is directly correlated with the increase in EPC numbers and measures of EPC function (Higashi, Matsuoka et al 2010).…”
Section: Dyslipidemiamentioning
confidence: 99%